PENGGUNAAN BAHASA DALAM MENGEKSPRESIKAN EMOSI KEGEMBIRAAN DALAM FILM TWILIGHT SAGA OLEH STEPHENIE MEYER SUATU ANALISIS PSIKOLINGUISTIK - WATUNA, EDWARD (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT Â This research entitled â€œPenggunaan Bahasa dalam Mengekspresikan Emosi Kegembiraan dalam Film Twilight Saga Oleh Stephenie Meyerâ€. Emotion associated with the feeling experienced by someone. Emotion emerged in a person who often disclosed with various expressions such as sad, happiness, angry, and love. Emotion that is given to certain feelings affect how to act. This is caused by the emotion which is the dominant factor affecting a personâ€™s act. Emotions are essentially a form of communication one. When someone in emotional, it means he is trying to convey the message to others. Based on this background, the writer is able to formulate the problem are what kind of gestures and languages people used in expressing happiness in the film Twilight Saga. The objectives of this research are to identify, analyze, and describe the gestures and languages used when people express happiness in the film Twilight Saga. This research was taken in the film Twilight Saga which consists in five part, they are Twilight,New moon,Eclipse, BreakingDawn Part 1, and Breaking Dawn Part 2. The researcher uses qualitative approach in order to find out the gestures and languages when people used in express their happiness. There are three steps that the writer do, they are preparation, collecting data, and analyzing data. The results of this research show that there are some expressions that could be found in expressing the feeling of happiness followed by the posture and gesture support Digagunarsa et al., theory about emosional expression. Â Keyword: Language, Happiness, Posture, Gesture, Twilight Saga